Viscum album L. Extracts Protects HeLa Cells against Nuclear and Mitochondrial DNA Damage - Önay-Uçar, Evren (Hindawi Publishing Corporation, 2012)
Viscum album L. is a semiparasitic plant grown on trees and widely used for the treatment of many diseases in traditional and complementary therapy. It is well known that some activities of Viscum album extracts are varied depending on the host trees, such as antioxidant, apoptosis-inducing, anticancer activities of the plant. The aim of the present study is to examine the comparative effects of methanolic extracts of V. album grown on three different host trees (locust tree, lime tree, and hedge maple tree) on H(2)O(2)-induced DNA damage in HeLa cells. Oxidative damage in mitochondrial DNA and two nuclear regions was assessed by QPCR assay. The cells were pretreated with methanolic extracts (10 μg/mL) for 48 h, followed by the treatment with 750 μM H(2)O(2) for 1 hour. DNA damage was significantly induced by H(2)O(2) while it was inhibited by V. album extracts. All extracts completely protected against nuclear DNA damage. While the extract from lime tree or white locust tree entirely inhibited mitochondrial DNA damage, that from hedge maple tree inhibited by only 50%. These results suggest that methanolic extracts of V. album can prevent oxidative DNA damage, and the activity is dependent on the host tree.